Assessing the Impact of a Minimum Income Scheme in the Basque Country - Sara de la Rica; Lucía Gorjón (Institute of Labor Economics (IZA), 2017)
In this paper we assess the impact of a Minimum Income Scheme (MIS) which has been operating in the Basque Country, one of Spain's 17 regions, for more than twenty years. In particular, we test whether the policy delays entry into employment for recipients. In addition, we test the efficacy of policies aimed at enabling recipients of the MIS to re-enter employment. Our results indicate that on average the Minimum Income Scheme, in addition to preventing social exclusion by providing financial support, does not delay entry into employment. However, the impact differs from one demographic group to another. Furthermore, Active Labour Market Policies designed for this group, in particular training, have a strong positive impact on finding a new job.
Keywords: C14; C21; C52; 330; minimum income schemes; active labour market policies; poverty; inverse probability weighting; propensity score matching